2021
DOI: 10.1097/mao.0000000000003042
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Predictors of Increased Length of Stay After Resection of Vestibular Schwannoma Using Machine Learning

Abstract: Objective: To evaluate the predictors of prolonged length of stay (LOS) after vestibular schwannoma resection. Study Design: Retrospective chart review. Setting: Tertiary referral center. Patients: Patients who underwent vestibular schwannoma resection between 2008 and 2019. Interventions: Variables of interest included age, body mass index, comorbidities, symptoms, previous intervention, microsurgical approach, extent of resection, operative time, preoperative tumor volume, and postoperative complications. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Nine studies evaluated the relationship between obesity and postoperative CSF leaks [1618, 2226, 29]. Six studies described the relationship between obesity and postoperative LOS [19, 20, 22, 24, 26, 28]. Five papers studied the influence of obesity on readmission and reoperation rates [20, 21, 24, 25, 27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies evaluated the relationship between obesity and postoperative CSF leaks [1618, 2226, 29]. Six studies described the relationship between obesity and postoperative LOS [19, 20, 22, 24, 26, 28]. Five papers studied the influence of obesity on readmission and reoperation rates [20, 21, 24, 25, 27].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies included in this review evaluated the impact of obesity on postoperative LOS [19,20,22,24,26,28]. Only one study demonstrated that obesity was associated with a longer LOS using the ACS-NSQIP database [26].…”
Section: Length Of Hospital Staymentioning
confidence: 99%
“…Thirty three articles were excluded due to predicting only pathological features, e.g., grade (n = 16), or differentiating between tumor entities (n = 8) [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Thirty four articles were excluded due to predicting only clinical parameters, e.g., tumor consistency (n = 7), response/treatment outcome (n = 12) or brain/bone invasion (n = 4) [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , …”
Section: Resultsmentioning
confidence: 99%
“…The overall prediction of the model on new data is then obtained by averaging across all decision trees. RFs have become increasingly popular machine learning models owing to their high degree of accuracy, ability to manage nonlinear data, and diminished likelihood of overfitting (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%